A descriptive epidemiological study of disability prevalence attributed to neurotic disorders in China. (February 2019) - Shen, Rui; Guan, Xing; Huang, Yueqin; Liu, Zhaorui; Chen, Hongguang; Zhang, Tingting; Ma, Chao
Highlights: The study was the first time that reported the disability prevalence attributed to neurotic disorder in China. The study estimated the association between the disability attributed to neurotic disorders and some main social-demographic characters. The prevalence of disability attributed to neurotic disorders is low in China and always leads to mild and moderate disability. Abstract: This study estimated the prevalence, correlates, severity and functional impairment of disabilities attributed to neurotic disorders in the Chinese population. Data from a representative national sample of 2, 526, 145 non-institutionalized residents were obtained from the Second China National Sample Survey on Disabilities (CNSSD) in 2006. The data were analyzed to estimate prevalence, correlates, severity and functional impairment of disability attributable to neurotic disorders by gender, age, region, and other key socio-demographic and economic factors. The disability prevalence attributed to neurotic disorders was 0.032% (805/2, 526, 145) in China. Women, rural residents, unemployed job status, low education level and those who were divorced or widowed showed higher prevalence rates than their counterparts. Proportions of mild, moderate, severe and extremely severe of neurotic attributed disability only accounted for 78.48%, 9.14%, 6.5% and 5.9%, respectively. Finally, these findings provide evidence that, prevalence rates of disability attributable to neurotic disorders vary greatly among different population groups and regions. Multiple disabilities including disability attributable to neurotic disorders can bring much more impairment to individuals than disability attributable to neurotic disorder only.